In-Plane Shear Characterization of Unidirectional Fiber Reinforced Thermoplastic Tape Using the Bias Extension Method - Brands, D.; Wijskamp, S.; Grouve, W. J. B.; Akkerman, R. (Frontiers in Materials, 2022)
Through an improved characterization methodology this work contributes to better prediction quality in composite forming simulations for unidirectional thermoplastic composites. Better understanding of the forming behavior will aid in the adoption of these lightweight materials in aerospace applications. The bias extension method was implemented and applied to cross-ply laminates from unidirectional carbon fiber reinforced thermoplastic materials to characterize the in-plane shear deformation resistance of the molten material. Two commercially available materials were characterized at three rates and three temperatures. The shear deformation was measured directly on the specimen throughout the test using a video extensometer, avoiding the use of the pin-jointed net assumption to relate deformation to the clamp displacement. In addition, the distribution of shear deformation over the specimen surface was characterized after the test using image analysis. The observed deformation was similar to the typical deformation for woven materials, with some agreement to the pin-jointed net assumptions but also some identified deviations. Localization of shear deformation along the fiber direction of the outer ply was observed to occur at approximately 15° shear angle. The proposed bias extension method directly relates the measured force to the deformation on the specimen, ensuring the characterization of the correct deformation mechanism. This key benefit of the bias extension method solves a common issue found in other characterization methods for inplane shear on molten material.